Gender differences in general mental health, smoking, drinking and chronic diseases in older adults in Jilin province, China. (May 2017) - Wang, Shibin; Ungvari, Gabor S.; Forester, Brent P.; Chiu, Helen F.K.; Wu, Yanhua; Kou, Changgui; Fu, Yingli; Qi, Yue; Liu, Yawen; Tao, Yuchun; Yu, Yaqin; Li, Bo; et al.
Abstract: There is little information on gender differences in general mental health, smoking, drinking and chronic diseases in Chinese elderly. We examined the gender differences in general mental health, smoking, drinking and a number of chronic diseases in a large Chinese old population. Multistage stratified cluster sampling was used in this cross-sectional study. A total of 4115 people (2198 women; 1917 men) aged between 60 and 79 years were included and their general mental health, smoking, drinking and chronic diseases were recorded with standardized assessment tools. Multivariate analyses revealed that women were less likely to be current smokers and frequent drinkers, but had higher prevalence of poor mental health compared with their male counterparts. In addition, the prevalence rate of chronic diseases and multi-morbidities were higher in women than that in men (both p values <0.05). Health professionals and policy makers need to pay special attention to the common chronic diseases and poor mental health in older women and higher prevalence of smoking and drinking in men. Highlights: Little is known about gender differences in health status in Chinese elderly. Chronic disease and poor mental health were more common in old women The prevalence of smoking and drinking were higher in old men.